2014
DOI: 10.1523/jneurosci.3776-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Signaling in the VTA Links the Drug-Dependent State to Drug Withdrawal Aversions

Abstract: Drug administration to avoid unpleasant drug withdrawal symptoms has been hypothesized to be a crucial factor that leads to compulsive drug-taking behavior. However, the neural relationship between the aversive motivational state produced by drug withdrawal and the development of the drug-dependent state still remains elusive. It has been observed that chronic exposure to drugs of abuse increases brain-derived neurotrophic factor (BDNF) levels in ventral tegmental area (VTA) neurons. In particular, BDNF expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…3). The incubation effect, wherein relapse is amplified after longer periods of abstinence, involves the VTA-accumbens pathway (Bahi et al, 2008; Graham et al, 2007; Grimm et al, 2003; Li et al, 2013; Lu et al, 2004a), at least for cocaine and perhaps also opiates, though there are conflicting reports (Koo et al, 2012; Vargas-Perez et al, 2009, 2014). Some evidence supports the importance of accumbens subregions in BDNF’s effects, with the shell being pro-relapse, but the core being capable of both pro-relapse and pro-extinction functions (Horger et al, 1999; Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). The incubation effect, wherein relapse is amplified after longer periods of abstinence, involves the VTA-accumbens pathway (Bahi et al, 2008; Graham et al, 2007; Grimm et al, 2003; Li et al, 2013; Lu et al, 2004a), at least for cocaine and perhaps also opiates, though there are conflicting reports (Koo et al, 2012; Vargas-Perez et al, 2009, 2014). Some evidence supports the importance of accumbens subregions in BDNF’s effects, with the shell being pro-relapse, but the core being capable of both pro-relapse and pro-extinction functions (Horger et al, 1999; Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, these data stand in stark opposition with earlier work from Vargas-Perez et al (2009), who found that VTA BDNF neither opposes nor facilitates morphine reward, but rather switches the mechanism for opiate reward from a dopamine-independent to a dopamine-dependent one. This occurs through BDNF’s reversal of GABA currents in VTA neurons from inhibitory to excitatory, and this effect is thought to underlie the negative aversive state associated with opiate withdrawal (Vargas-Perez et al, 2014). …”
Section: Bdnf and Opiate Seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple lines of evidence have demonstrated that BDNF plays an important role in learning and memory in different brain regions [14,15,33] . Moreover, recent studies have found that the BDNF signaling pathway contributes to cocaine seeking [22,23,25,34,35] . Whether the BDNF signaling pathway participates in the formation of aversive memories associated with morphine withdrawal remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, brain regions associated with reward and affective behaviors have also been implicated [13]. It has been shown that chronic opioid administration in rodents promoted GABA-mediated excitation [14] and loss of neuronal inhibition via reduction of KCC 2 currents in the ventral tegmental area [15]. Furthermore, acute morphine withdrawal in rats increased c-Fos expression in dopaminergic neurons within nucleus accumbens shell in mice [16], and phosphorylation of NMDARs in the accumbens [17].…”
mentioning
confidence: 99%